Estimation of energy demand and carbon dioxide emissions in Philippine road transport using inter-regional passenger and freight O-D data - Sundo, Marloe B. (College of Engineering, University of the Philippines Diliman, 2016)
Carbon dioxide (C02) from the transport sector is by far considered as the major contributor of Greenhouse gas (GHG) emission into the atmosphere. Given the increasing scientific understanding of the threat of global warming and climate change and the decline oil production to meet the demand, many countries are now finding ways to make energy consumption efficient to reduce GHG emissions. One major considerations pertaining to transportation planning and development is to know the amount of energy consumption and emissions produced from the transportation sector during its operation. Thus, this study was proposed to develop a new methodology of estimating energy demand and CO2 emissions from the Philippine road transport using inter-regional passenger and freight flow through some mathematical approach. Reference or "Do-Nothing" scenario for energy demand and CO2 emission were compared with three fuel sensitive policy options. The study shows that total energy demand for the inter-regional road transport under the reference scenario was about 4,071.69ktoe in 2013 to 5,541.54ktoe in 2030 and to about 7,834.55ktoe in 2050. Also shows the reference scenario substantially increased the overall inter-regional carbon dioxide emissions from 12.61 MtC02 in 2013 to 24.26 MtC02 in 2050. Public mode of transport was found to have contributed much of these emissions for inter-regional travel as compared with private and freight. Fuel sensitive policy options were compared in terms of overall reduction in CO2 emissions. Shifting to better alternative fuel for private and public transport yield the highest reduction of C02 emissions with 39.49% and 55.52% in 2030 and 2050, respectively. Switching to revitalized and modernized inter-regional railway system provide the second highest CO2 emissions reduction with 23.24% and 48.37% in 2030 and 2050, respectively. Better logistic management system for freight transport ranked third in reducing C02 emissions with 4.405 and 13.92% in 2030 and 2050, respectively. Implementation of HSH-I yield the least impact in reducing CO2 emissions with -0.17% and 7.65% in 2030 and 2050 respectively. As expected, the combinations of all selected policy scenarios provide the highest reduction of CO2 emissions as compared with individual policy implementation with 52.71% and 74.24% in 2030 and 2050, respectively. The study also suggests that the government's interventions in reducing carbon dioxide emissions should be more directed towards public and freight transport as these two sectors were found to have substantially contributed to the overall energy demand and CO2 emissions as compared with private transport for inter-regional travel.